Editorial: Solar neighborhood planning: optimize solar energy use in cities through the digitalization of the built environment - Desthieux, Gilles; Manni, Mattia; Lobaccaro, Gabriele; Hachem-Vermette, Caroline; Croce, Silvia; Thebault, Martin; Kanters, Jouri (Frontiers in Built Environment, 2024)
Graphical Abstract